Developing Professional-Pedagogical Competence in Future Teachers of Visual Arts (Zien Journal of Social Sciences and Humanities, 2023)
Purpose of the study is to identify, theoretically substantiate, and experimentally test the pedagogical conditions for developing professional-pedagogical competence in future teachers of visual arts based on a polyartistic approach